A tangible user interface design guideline to support learning for children with Dyslexia - Nurul Izzah, Abdul Aziz (2023)
Tangible Interaction (TI) is gaining popularity as a means of supporting learning using physical tangible objects with the interaction of digital space. This approach provides a multisensory experience to children with dyslexia, making the learning session more meaningful. Therefore, TI has the potential to provide multisensory features when using a computer, and as a result, Tangible User Interfaces (TUIs) have emerged. Current TUIs frameworks offer very few design guidelines or tools specifically tailored to meet the needs of children with dyslexia. Previous studies have highlighted that the framework provides data-centred views that only focus on combining physical and digital representations. However, these frameworks do not consider the unique needs and abilities of children with dyslexia, such as their difficulties with reading, writing, and processing visual information. Thus, this study proposes effective TUI design guidelines for children with dyslexia to support learning to read. The study was conducted in five phases: 1) theoretical study; 2) identification of TUIs design components; 3) framework and design guideline development; 4) prototype development; and 5) the validation of TUIs design guideline. A prototype was developed to evaluate the effectiveness of TUIs design guideline during learning activities with children with dyslexia. Seven experts verified the TUIs framework and its design guideline. This study contributed to improving the present design guideline of TUIs. The positive feedback and improvement in learning outcomes from the children with dyslexia validated the effectiveness of the TUIs design guideline. The findings of this study contribute theoretically and practically to the field of TUIs and HCI. They are expected to assist researchers and developers in developing tangible systems that meet the requirements of children with dyslexia. The system developers would be able to understand the needs of children with dyslexia with a clear design guideline for better learning outcomes and improved educational experiences.